Ферма. Зверская кража - Зубенко Екатерина Сергеевна (Самый прикольный детектив, 2020)
Экземпляры: ф.10 (20211221) / Инвентарный номер: 61497 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: З-91 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-4